Strategi Pemasaran Politik Calon Legislatif Partai Kebangkitan Bangsa Dalam Pemilu Legislatif 2014 Pada PKB Kota Semarang - M.Agus Nurkholis; Puji Astuti; Rina Martini (Journal of Politic and Government Studies, 2015)
ABSTRACTION On the implementation of legislative general election in 2014, each candidate legislature was expected to maximize his political marketing strategies alone. It was because a political party only gave directions without forming a mass of support for each candidate legislative. In semarang city, PKB experienced inconsistency of the ballot in every convention of legislative election. In 2004 , PKB got 66.337 votes of sending 6 deputy legislative and in 2009 the ballot of PKB decreased drastically which only got 25.063 votes ( only sent 1 deputy legislative ). The inconsistency of this ballot was caused by the presence of the influence of internal conflicts the party protracted and the implementation of marketing strategy of the political less maximal. Whereas, general election in 2014, PKB experienced an increase in voting became 66.400 and sent 4 vice legislatives. That is why the statement of the problem in this research is “how are the PKB candidates’ political marketing strategies in the legislative general election 2014 espescially in Semarang city? and what are the reasons of the candidate using that political marketing strategies ?This research using qualitative method with type of the research is descriptive analytical because this research is done by interviewing and providing analysis of the ilustration of the indications and the facts in the field. So it can be seen how the strategy of political marketing conducted by legislative candidates PKB of semarang city to face legislative election in 2014.The results of this research show a model of political marketing through the socialization door to door to be one of the main strategies the successful of some legislative candidates PKB in semarang city to obtain the support of a mass. This is because through the socialization door to door, legislative candidates can interact with the society directly, give understanding and instruction to vote the ballot. Then, one of the key victory of PKB legislative candidates semarang city in legislative general elections 2014 is marketing political by doing socialization door to door and by process of monitoring and evaluating of the successful performance of the team. The process of monitoring and evaluating this performance is in order to marketing team able to maximize the process of political marketing and they don’t move to other legislative candidate. Then, one thing that causes the failure of some legislative candidates PKB semarang city is lack of cooperation and coordination between legislative candidates and lack of the process of supervision of team success.So, it is causing the marketing political less maximal and there are differentiation in the ballot legislative candidates who are in one local election significantly. Hence, in the process of political marketing, each candidate legislature is expected to establish cooperation and coordination with other legislative candidates as well as monitoring and evaluating of the successful performance of the team routinely. The goal is in order to legislative candidates able to minimize competition between legislative candidates in internal political parties and maximize his political marketing strategies in the base of support areaKeywords : Legislative General Election, Legislative Candidate, Political Marketing Model.